1997
DOI: 10.1136/bmj.314.7076.281
|View full text |Cite
|
Sign up to set email alerts
|

Women's need for information before attending genetic counselling for familial breast or ovarian cancer: a questionnaire, interview, and observational study

Abstract: There is growing consensus that treatment of cardiovascular risks should be based on multiple rather than single factors and on absolute rather than relative risks. Thresholds for treatment should reflect the level of absolute risk at which the benefits and hazards of treating outweigh the benefits and hazards of not treating. Once a decision has been made to initiate a treatment programme, clinicians need to know the patient's absolute risk. At this level of risk, do the benefits of treatment outweigh the haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 7 publications
3
65
0
Order By: Relevance
“…The finding that the vast majority of women come to genetic counselling to obtain information about prevention, surveillance and risk information for themselves and for their children is similar to that reported by other studies (Julian-Reynier et al, 1996Hallowell et al, 1997;). Four out of five women expected a genetic test, over a third expected a physical examination (33%) and just under half expected a referral for screening (43%).…”
Section: Were Women's Expectations Of Genetic Counselling Met?supporting
confidence: 85%
See 1 more Smart Citation
“…The finding that the vast majority of women come to genetic counselling to obtain information about prevention, surveillance and risk information for themselves and for their children is similar to that reported by other studies (Julian-Reynier et al, 1996Hallowell et al, 1997;). Four out of five women expected a genetic test, over a third expected a physical examination (33%) and just under half expected a referral for screening (43%).…”
Section: Were Women's Expectations Of Genetic Counselling Met?supporting
confidence: 85%
“…These categories were based on (i) the National Health and Medical Research Council's Guidelines on the Familial Aspects of Cancer: A Guide to Clinical Practice (NH and MRC, 1999), (ii) an Australian survey of clinical geneticists/ genetic counsellors describing their practice (Lobb et al, 2001) and (iii) studies that identified women's expectations of the genetic counselling session (Hopwood et al, 1993;Julian-Reynier et al, 1996Hallowell et al, 1997;Michie et al, 1997;Veach et al, 1999;Brain et al, 2000).…”
Section: Coding Of Transcripts Of Audio-tapesmentioning
confidence: 99%
“…Unlike population-based studies (see above), studies investigating genetic knowledge and attitudes in patients usually concentrate on specific disease-related issues [e.g., [15][16][17][18]. The present study aimed to investigate knowledge and attitudes related to genetics and genetic testing in general, among patients with chronic illnesses (e.g., diabetes, heart disease, musculoskeletal disease).…”
Section: Introductionmentioning
confidence: 99%
“…Both UK and Dutch counselees who are the first in their family to request cancer genetic counselling (probands) have unrealistic expectations or do not know what to expect (Metcalfe et al 2007;Bernhardt et al 2000;Hallowell et al 1997;Pieterse et al 2005b). Many expect to be offered a DNA-test independent of their disease status and risk profile (Metcalfe et al 2007;Hallowell et al 1997;Pieterse et al 2005c). Also, many people in the UK and the NL lack basic genetic knowledge (Henneman et al 2004;Calsbeek et al 2007;Morren et al 2007;Mesters et al 2005;Walter et al 2004).…”
Section: Introductionmentioning
confidence: 99%